The role of macrophages in rosacea: implications for targeted therapies - Liu, Yi; Zhou, Yin; Chu, Chenyu; Jiang, Xian (Frontiers in Immunology, 2023)
Rosacea, a widespread chronic skin condition, may be influenced by macrophages, key immune cells in the skin, although their exact role is not yet fully understood. This review delves into the function of macrophages, their potential contribution to rosacea pathogenesis, current treatments, and promising macrophagetargeted therapies. It concludes by identifying knowledge gaps and potential areas for future rosacea research.Method: Method: Leveraging systematic and narrative literature review techniques, we conducted a comprehensive search of databases such as PubMed, Embase, and Web of Science. Utilizing keywords like "rosacea," "macrophages," among others, we targeted English articles from the last five years (2018-2023). Reference lists of relevant articles were manually checked for additional studies. Only articles emphasizing macrophages' role in rosacea and/or development of related therapies, and published within the specified timeframe were included.The systematic search of electronic databases yielded a total of 4263 articles.After applying the inclusion and exclusion criteria, 156 articles were selected for inclusion in this review. These articles included original research studies, review articles, and clinical trials that focused on the role of macrophages in rosacea and/or the development of macrophage-targeted therapies for the disease. The selected articles provided a comprehensive and up-to-date overview of the current state of research on macrophages in rosacea, including their function in the skin, the potential mechanisms through which they may contribute to rosacea pathogenesis, and the current treatments and therapies available for the disease. Additionally, the articles identified gaps in knowledge regarding the role of macrophages in rosacea and suggested potential areas for future research.This literature review emphasizes the important role that macrophages, vital immune cells in the skin, may play in the pathogenesis of rosacea, a common chronic inflammatory skin disorder. The selected studies suggest potential mechanisms by which these cells might contribute to rosacea progression, although these mechanisms are not yet fully understood. The studies also spotlight current rosacea treatments and illuminate the promising potential of new macrophage-focused therapies.